Efektivitas Ekstrak Etanol Daun Karanda (Carissa carandas L.) Terhadap Histopatologi Hepar Tikus Putih (Rattus norvegicus) Diabetes Melitus - Parinduri, Ayu Nurhabibah; Febriani, Husnarika; Syukriah, Syukriah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Diabetes Mellitus (DM) is a metabolic disease characterized by impaired insulin secretion in the target organs, especially hepar. Diabetes mellitus can be treated by giving traditional medicine extract of ethanol karanda leaves (Carissa carandas). The purpose of the study was to find out the effectiveness of karanda leaf ethanol extract on the morphology and histopathology of hepar white mouse diabetes mellitus. The study used a Complete Random Design (RAL) with 6 treatments and 4 repeats. The treatment consists of normal control (feed and drink), negative control (120mg/kgBB), positive control (120mg/kgBB+glibenklamid 0.45mg/kgBB, and treatment of karanda leaf ethanol extract at graded doses of 500mg/kgBB, 750mg/kgBB, and 1000mg/kgBB. The manufacture of hepar histology uses the paraffin method with hematoxylin-eosin (HE) staining. The data was analyzed using the ANOVA test at a 5% confidence level. The results showed significant differences (p0.05) in normal cells, parenkimatous degeneration, hydropic degeneration, and necrosis and had an effect on improving the diameter of the centralist vein. Administration of ethanol extract of karanda leaves dose of 750mg / kgBB has the potential as a hepatoprotector in white rats with diabetes mellitus. Further testing is needed regarding the optimum limit of the dose of karanda leaf ethanol extract (Carissa carandas) and the toxicity test of karanda leaves.